Desenvolvimento de ferramenta de gestão para avaliação de risco hídrico: aplicação no segmento mínero-metalúrgico no Brasil - Thaiza Clemente Couto (2016)
Although the governance of water in the industrial sector has evolved greatly in recent years, mainly due to efforts to decrease costs, ensuring social license to operate and to prevent the risks associated with water supply, management of water risk in Brazil is still a challenge. Thus, this project aims to develop a Water Risk Assessment Tool (FARH) for the metallurgical and mining sector. The structure of the FARH tool was developed based on input blocks, processing and output data. The objective is to generate a dashboard contemplating the characterization of the watershed in relation to the degree of water stress (Y-axis), characterization of the water management of the enterprise (X-axis) and the definition of the enterprise level of dependency in relation to water resources. The tool was applied on a pilot level in nine (09) projects located in the states of Minas Gerais, Goias and Sao Paulo, with the proposed criteria considered adherent to the reality of these operations. With the validation of the FARH criteria, data platforms MS Excel macros was developed for computerization of its application, which will allow the analysis of water risk in an automated way. The dashboard make possible a consolidated view of the data, providing comparisons between different operations and providing technical basis for prioritizing actions and allocation of resources within the organization. Additionally, the results can be incorporated into the strategic planning of projects regarding the corporate governance, serving as a subsidy for the implementation of the water management and contingency plan on projects for the metallurgical and mining sector.